A construção e importância do planejamento plurianual na gestão municipal de Mojuí dos Campos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This research aims to address and present the formation process of a Multi-Year Plan (PPA) in the context of a newly created municipality, and list the importance of this political instrument in the consolidation of management in Mojuí dos Campos. To achieve this, we will seek a theoretical survey of authors within the PPA theme of political tools to promote good public management, contextualize and study the area of study (Mojuí dos Campos) in order to, with the capture of this information, build the interweaving of the tools of Management as a PPA in the consolidation of management within a newly created municipality. The methodology adopted for the development of the research is based on a case study, supported by a bibliographical and documentary research, in addition to descriptive research. Mojuí dos Campos is a newly emancipated municipality, which has undergone and is still undergoing changes and the construction of its social, cultural, economic and political system, and in view of this, public management actions are planned with the common good of its population in mind. , and for this purpose auxiliary instruments are necessary, such as the PPA, and this tool has its first version from 2014-2017 in the municipality, and despite its defined macro-objectives, there are still essential sectors that need to be rethought and further explored for the common good of its population, therefore, it is crucial that the latest versions are rethought.
Keywords: Plano Plurianual; Mojuí dos campos; Gestão Pública; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS